2010
DOI: 10.1242/jeb.039644
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation state of the Na+–K+–Cl− cotransporter (NKCC1) in the gills of Atlantic killifish (Fundulus heteroclitus) during acclimation to water of varying salinity

Abstract: SUMMARYEuryhaline teleosts such as Atlantic killifish (Fundulus heteroclitus) are able to acclimate to changing environmental salinity by tightly regulating NaCl absorption and secretion across their gills. Many studies have examined the mechanisms responsible for long-term (days) salinity acclimation; however, much remains unknown about the mechanisms of acute (hours) salinity acclimation. In this study, we tested the hypotheses that phosphorylation of the Na + -K + -Cl -cotransporter (NKCC1) located in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 43 publications
2
23
0
1
Order By: Relevance
“…Juvenile alewife salinity acclimation in freshwater-acclimated individuals. This might be an inactive nonphosphorylated pool of NKCC1 that could be quickly activated for an acute response upon exposure to elevated salinities (Flemmer et al, 2010). Notably, the proportional increase in NKCC1 abundance upon seawater acclimation was much greater than that of NKA, further suggesting that NKA isoforms have a role in ion absorption.…”
Section: Discussionmentioning
confidence: 96%
“…Juvenile alewife salinity acclimation in freshwater-acclimated individuals. This might be an inactive nonphosphorylated pool of NKCC1 that could be quickly activated for an acute response upon exposure to elevated salinities (Flemmer et al, 2010). Notably, the proportional increase in NKCC1 abundance upon seawater acclimation was much greater than that of NKA, further suggesting that NKA isoforms have a role in ion absorption.…”
Section: Discussionmentioning
confidence: 96%
“…The rapid upregulation of the two proteins likely results from de novo protein synthesis by using an existing pool of mRNA. Similarly, rapid increase in NKCC1 protein has been observed in the gills of Atlantic killifish when transferred from fresh to seawater [< 6 hours, [43]]. Therefore, the fast upregulation of transporter proteins and their regulatory kinases will allow cells to quickly acclimate to an altered osmotic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, killifish are a valuable model for elucidating the mechanisms of acclimation to osmotic stress, and the effects of environmental toxicants on acclimation (Burnett et al, 2007; Marshall et al, 2005; Scott et al, 2006; Shaw et al, 2010; 2007b; 2008; Stanton et al, 2006). Most of the studies examining acclimation to osmotic stress in killifish have focused on the regulation of ion transport, such as transport of Cl - and Na + by the gill and opercular membrane (Flemmer et al, 2010; Marshall et al, 2005; Scott et al, 2008; Shaw et al, 2007a; 2008; Wood and Marshall 1994; Zadunaisky et al, 1995). These studies have demonstrated that in seawater, marine teleosts drink copious amounts of water, thus they must excrete the NaCl that is absorbed by the gastrointestinal tract to maintain plasma concentrations of Na + and Cl - (i.e., plasma osmolality).…”
Section: Introductionmentioning
confidence: 99%